Nonlinear Robust Control for Spacecraft Attitude - Wang Lina; Li Zhi (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Nonlinear robust control of the spacecraft attitude with the existence of external disturbances is considered. A robust attitude controller is designed based on the passivity approach the quaternion representation, which introduces the suppression vector of external disturbance into the control law and does not need angular velocity measurement. Stability conditions of the robust attitude controller are given. And the numerical simulation results show the effectiveness of the attitude controller.DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3477